Efeito da nutrição materna sobre o perfil da fibra muscular, carcaça e carne de cordeiros criados em pastos de capim Marandu - CAMILA DE GODOY (2023)
The objective of this study was to compare the effect of different supplementation strategies for ewes in the gestation and lactation phases, raised in Brachiaria brizantha cv. Marandu, on the productive performance, carcass composition, meat quality and muscle fiber characteristics of their lambs. Sixty F1 Texel ewes, with an average weight of (52 ± 6.48 kg), were used in a completely randomized design, distributed in two treatments (30 ewes per treatment) with different levels of protein energy supplementation for the care of 7, 5% and 15% of the nutritional requirement at different physiological stages. In total, 46 lambs were born, (n = 25) females and (n = 21) males, with (4.40±0.50 kg) birth weight, the females were reintroduced into the herd and the males were evaluated. The diet for the lambs in the growing phase consisted of protein concentrate provided in creep-feeding. In finishing, the lambs received a daily protein concentrate supplement at 1.6% of body weight. The animals were kept on Marandu grass pasture throughout the experimental phase. The lambs were slaughtered at six months of age with an average of (40 kg). Maternal diets did not influence weight gain, body condition score and in vivo measurements of lambs. For carcass traits hot carcass weight (PCQ), cold carcass weight (PCF), hot carcass yield (RCQ), cold carcass yield (RCF), conformation, finish, ribeye area (AOL), subcutaneous fat thickness (EGS) and cut yield showed no significant difference (P<0.05) between maternal treatments. There was no effect between maternal groups for pH, meat color and fat, shear force, sarcomere length, myofibrillar fragmentation index and centesimal composition in lamb meat. However, there was a significant effect (P<0.05) of maternal diet on the area and amount of fiber in the longissimus thoracis muscle, lambs from the 7.5% group had larger areas of fibers (oxidative, glycolytic and intermediary). For the amount of fiber, lambs from the 15% group had more glycolytic fibers while the 7.5% group had more oxidative fibers. The use of protein-energy supplementation for ewes on pasture during pregnancy and lactation was able to change the characteristics of muscle fibers in the fetus. We recommend the use of a level of 7.5% of the nutritional requirement for ewes kept on pasture, as it was enough to guarantee a productive performance without changes in carcass and meat characteristics of lambs raised on pastures of Brachiaria brizantha cv. Marandu.